Unveiling students’ understanding of autonomy: puzzling out a path to learning beyond the efl classroom (2008)
This paper aims at reporting a research project on students’ understandings of autonomy evidenced in their learning experiences while in the EFL classroom and outside of it in a Colombian public university. This research study is conceived as a response to the new paradigm we are exposed to in our social and educational settings in which decision making becomes a key feature of individuals. Data were gathered through field notes, video recordings, a questionnaire, interviews, students’ logs and audio-recorded plenary sessions. The results of the study indicated that students conceived autonomy as an opportunity to find a key to learning beyond the classroom. When walking on this path, students faced a dilemma between detachment and teacher dependence; they showed independence in decision making taking advantage of learning opportunities beyond the classroom and engaging in reflection. They also constructed knowledge through experience and carried out learning self-evaluation processes. Key words: Autonomy, learning experiences, learning beyond the EFL classroom, self-evaluation Este artículo reporta un proyecto de investigación sobre las concepciones de autonomía de estudiantes evidenciadas en experiencias de aprendizaje de inglés dentro y fuera del aula de clase en una universidad pública colombiana. Este estudio de investigación responde al nuevo paradigma al que estamos expuestos en nuestro entorno social y educativo en el que la toma de decisiones es un elemento primordial para los individuos. Los datos se recolectaron mediante notas de campo, video-grabaciones y bitácoras de los estudiantes. Los resultados del estudio indican que los estudiantes conciben la autonomía como una oportunidad para su aprendizaje más allá del aula de clase. A lo largo de este camino, los estudiantes enfrentaron un dilema entre distanciamiento y dependencia del profesor y mostraron independencia al tomar decisiones utilizando oportunidades de aprendizaje fuera del aula de clase y reflexionar. Asimismo construyeron conocimiento a través de su experiencia y llevaron a cabo procesos de auto-evaluación. Palabras clave: Autonomía, experiencias de aprendizaje, aprendizaje fuera del aula de clase, autoevaluación